The structure of mixed nonionic surfactant monolayers at the air-water interface: the effects of different alkyl chain lengths. - Penfold, J; Staples, E; Tucker, I; Thomas, R; Woodling, R; Dong, C (2003)
The structure of mixed nonionic surfactant monolayers of monodecyl hexaethylene glycol (C10E6) and monotetradecyl hexaethylene glycol (C14E6) adsorbed at the air-water interface has been determined by specular neutron reflectivity. Using partial isotopic labeling (deuterium for hydrogen) of the alkyl and ethylene oxide chains of each surfactant, the distribution and relative positions of the chains at the interface have been obtained. The packing of the two different alkyl chain lengths results in structural changes compared to the pure surfactant monolayers. This results in changes in the relative positions of the alkyl chains and of the ethylene oxide chains at the interface. The role of the alkyl chain length is contrasted with that of the ethylene oxide chain length, determined from results reported previously on the nonionic surfactant mixture of monododecyl triethylene glycol (C12E3) and monododecyl octaethylene glycol (C12E8).